2016
DOI: 10.1016/j.copbio.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Engineering approaches to study fibrosis in 3-D in vitro systems

Abstract: Fibrotic diseases occur in virtually every tissue of the body and are a major cause of mortality, yet they remain largely untreatable and poorly understood on a mechanistic level. The development of anti-fibrotic agents has been hampered, in part, by the insufficient fibrosis biomimicry provided by traditional in vitro platforms. This review focuses on recent advancements toward creating 3-D platforms that mimic key features of fibrosis, as well as the application of novel imaging and sensor techniques to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Here we provide a human lung fibrotic microtissue array that allows multi-parameter, phenotypic screening of the anti-fibrosis drug candidates in a relatively high-throughput manner. The adoption of the microtissue array format offers orders of magnitude scale-up advantages over tissue biopsy samples and conventional engineered tissues 10 , 11 , leading to improved experimental throughput. Further integration of the microtissue array with multi-well plate enabled parallel analysis of multiple drug conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Here we provide a human lung fibrotic microtissue array that allows multi-parameter, phenotypic screening of the anti-fibrosis drug candidates in a relatively high-throughput manner. The adoption of the microtissue array format offers orders of magnitude scale-up advantages over tissue biopsy samples and conventional engineered tissues 10 , 11 , leading to improved experimental throughput. Further integration of the microtissue array with multi-well plate enabled parallel analysis of multiple drug conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Because SHG does not require tissue fixation or staining, its use could advance current efforts to engineer fibrotic environments in vitro [ 50 ]. The combination of fibrosis tissue engineering with SHG may offer the ability to gain insight into fibrogenic processes through the non-invasive visualization of ECM dynamics in living cultures [ 51 ]. Recent work has also shown that SHG imaging of collagen alterations may be combined with machine learning algorithms to characterize the extent of fibrosis in clinical samples, as well as provide automated, high-throughput diagnoses of fibrotic disease [ 52 56 ]…”
Section: Discussionmentioning
confidence: 99%
“…In case of cardiac disease, the heart is subject to changes in composition and structure, often leading to cardiac fibrosis. While at first, fibrogenesis is an effective mechanism of tissue repair, ongoing adverse remodeling will lead to a decrease in cardiac functionality and eventually to the development of heart failure [ 1 ]. To halt or reverse this process, anti-fibrotic therapies are being developed [ 2 ], so far with limited success, due to the fact that the extent and distribution of fibrosis vary according to the underlying pathology.…”
Section: Introductionmentioning
confidence: 99%